Genetic variation within and relationships among populations of Asian water buffalo (Bubalus bubalis) - Barker, J.S.F.; Tan, S.G.; Selvaraj, O.S.; Mukherjee, T.K. (Blackwell Publishing, 1997)
Genetic variation at 53 protein-coding loci (25 polymorphic) was analysed for 17 water buffalo populations - 12 swamp, three Lankan and two of the Murrah breed (river type), to determine the magnitude of genetic, differentiation and tim genetic relationships among the populations. In accord with previous cytological studies, the Lankan buffalo clearly are river type. Significant deviations from Hardy-Weinberg equilibrium were shown for a number of locus-population combinations, with all populations but one showing significant heterogeneity in these deviations among loci. By contrast, heterogeneity among populations for each locus was much less, indicating locus-specific deviations, which suggest selection affecting allele frequencies at some loci. There was significant genetic differentiation among populations of both the swamp and river types. The differentiation among the swamp populations may reflect the geography of south-east Asia and the presumed spread of the swamp buffalo through this region. Phylogenies derived from pairwise genetic distance estimates show the clear separation of swamp and river types, but the topology of the swamp populations shows rather poor consistently with their geographic locations. For at least one population (Australia), it is clear that bottleneck effects have distorted the phylogenetic topology. Average genetic distances for both the swamp and river types, as compared with previous studies of livestock breeds, show that the genetic differentiation of each of thirst sets of populations is of the same order of magnitude as that among well-recognized and established breeds of other species.